2011
DOI: 10.1063/1.3676170
|View full text |Cite
|
Sign up to set email alerts
|

Realization of a 33 GHz phononic crystal fabricated in a freestanding membrane

Abstract: Phononic crystals (PnCs) are man-made structures with periodically varying material properties such as density, ρ, and elastic modulus, E. Periodic variations of the material properties with nanoscale characteristic dimensions yield PnCs that operate at frequencies above 10 GHz, allowing for the manipulation of thermal properties. In this article, a 2D simple cubic lattice PnC operating at 33 GHz is reported. The PnC is created by nanofabrication with a focused ion beam. A freestanding membrane of silicon is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…It is hence not surprising that the ability to control and manipulate the flow of phonons has captured the interest of the scientific community. In recent years, it has been shown that the propagation of acoustic energy may be efficiently and even precisely controlled by novel sonic devices, bringing exciting and promising opportunities for sound management. Initially coined as PnCs, recent work aimed at manipulating acoustic propagation with structures having key components on the sub‐wavelength scale has led to the development of acoustic metamaterials.…”
Section: Polymer‐based Phononic Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…It is hence not surprising that the ability to control and manipulate the flow of phonons has captured the interest of the scientific community. In recent years, it has been shown that the propagation of acoustic energy may be efficiently and even precisely controlled by novel sonic devices, bringing exciting and promising opportunities for sound management. Initially coined as PnCs, recent work aimed at manipulating acoustic propagation with structures having key components on the sub‐wavelength scale has led to the development of acoustic metamaterials.…”
Section: Polymer‐based Phononic Structuresmentioning
confidence: 99%
“…Thus, low‐frequency PnC structures were mostly fabricated from metal or semiconductor material platforms. More recently, however, several different fabrication technologies have allowed for the significant reduction in the feature size of the structures, providing new means for an effective control of high frequency (f>1 MHz ) phonons in small‐form‐factor PnCs . In particular, polymer‐based PnCs with fine feature sizes have demonstrated successful control of very high frequency (f1 GHz ) hypersonic phonons …”
Section: Polymer‐based Phononic Structuresmentioning
confidence: 99%
“…Finally, other techniques have been employed to fabricate 2D PnCs, such as focused ion beam (FIB) milling, which has the advantage of direct substrate patterning, with no need of further pattern transfer. For instance, FIB milling was used to realize a PnC fabricated in a free‐standing silicon membrane and showing frequency bandgaps above 25 GHz. FIB milling can be used for other materials, especially those difficult to etch with dry etching techniques, such as LiNbO 3 .…”
Section: Fabrication Techniquesmentioning
confidence: 99%
“…In addition, the problem of contact between nanoparticles would be avoided. The fabrication of phononic band gap materials has already been explored for materials such as silicon or gallium arsenide [60] and phononic structures with a bandgap at 33 GHz and dimensions around 100 nm have been demonstrated [61]. To create phononic crystal structures in currently-used host materials such as Y 2 SiO 5 , Y 3 Al 5 O 12 or LiNbO 3 , thin films of those materials would be a prerequisite.…”
mentioning
confidence: 99%